Sex differences in self-regulation: an evolutionary perspective - Hosseini-Kamkar, Niki; Morton, J. Bruce (Frontiers in Neuroscience, 2014)
Bjorklund and Kipp (1996) provide an evolutionary framework predicting that there is a female advantage in inhibition and self-regulation due to differing selection pressures placed on males and females. The majority of the present review will summarize sex differences in self-regulation at the behavioral level. The neural and hormonal underpinnings of this potential sexual dimorphism will also be investigated and the results of the experiments summarized will be related to the hypothesis advanced by Bjorklund and Kipp (1996). Paradoxically, sex differences in self-regulation are more consistently reported in children prior to the onset of puberty. In adult cohorts, the results of studies examining sex differences in self-regulation are mixed. A few recent experiments suggesting that females are less impulsive than males only during fertile stages of the menstrual cycle will be reviewed. A brief discussion of an evolutionary framework proposing that it is adaptive for females to employ a self-regulatory behavioral strategy when fertile will follow.